(untitled) (Contemporary Education and Teaching Research, 2025)
The formation pathway of college students’ employment intentions is crucial for clarifying their employment logic, refining higher education vocational policies and methods, and enhancing their career competitiveness. Based on a review of domestic and international literature, this paper uses the Theory of Planned Behavior as a framework, combining interviews and sentence completion techniques, to investigate the formation pathways of employment intentions among Chinese college students.